Proactive management of extreme prematurity: Disagreement between obstetricians and neonatologists - Guinsburg, R.; Branco de Almeida, M. F.; Dos Santos Rodrigues Sadeck, L.; Marba, S. T M; Rugolo, Ligia Maria Suppo de Souza [UNESP]; Luz, J. H.; De Andrade Lopes, J. M.; Martinez, F. E.; Procianoy, R. S. (Springer Nature, 2012)
Objective: To verify, in extremely preterm infants, if disagreement between obstetricians and neonatologists regarding proactive management is associated with early death.Study Design: Prospective cohort of 484 infants with 23 0/7 to 266/7 weeks, without malformations, born from January 2006 to December 2009 in eight Brazilian hospitals. Pro-active management was defined as indication of ≥1 dose of antenatal steroid or cesarean section (obstetrician) and resuscitation at birth according to the international guidelines (neonatologist). Main outcome was neonatal death in the first 24 h of life.Result: Obstetricians and neonatologists disagreed in 115 (24%) patients: only neonatologists were proactive in 107 of them. Disagreement between professionals increased 2.39 times the chance of death in the first day (95% confidence interval 1.40 to 4.09), adjusted for center and maternal/neonatal clinical conditions.Conclusion: In infants with 23 to 26 weeks of gestation, disagreement between obstetricians and neonatologists, translated as lack of antenatal steroids and/or vaginal delivery, despite resuscitation procedures, increases the odds of death in the first day. © 2012 Nature America, Inc.
Keywords: Cardiopulmonary resuscitation; Cesarean section; Fetal viability; Infant newborn; Neonatal mortality; Steroids; steroid; cesarean section; cohort analysis; controlled study; female; gestational age; human; major clinical study; male; neonatology; newborn; newborn care; newborn mortality; obstetrics; outcome assessment; perinatal period; physician attitude; practice guideline; prematurity; prospective study; resuscitation; risk assessment; vaginal delivery; Adrenal Cortex Hormones; Analysis of Variance; Brazil; Cardiopulmonary Resuscitation; Cesarean Section; Cohort Studies; Confidence Intervals; Delivery, Obstetric; Female; Fetal Viability; Gestational Age; Humans; Infant Mortality; Infant, Newborn; Infant, Premature; Infant, Very Low Birth Weight; Intensive Care Units, Neonatal; Interprofessional Relations; Life Support Care; Logistic Models; Male; Neonatology; Obstetrics; Odds Ratio; Physician's Practice Patterns; Pregnancy; Prognosis; Prospective Studies; Treatment Outcome